Brazilian policies and strategies for rural territorial development in Mozambique: South-South cooperation and the case of ProSAVANA and PAA - Clements, Elizabeth Alice [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This thesis analyzes Brazil's present role in South-South development cooperation in Africa, focusing on the implementation and impact of Brazilian policies for rural territorial development in Mozambique. Specifically, two different programs for agricultural development-ProSAVANA and PAA Africa-are examined. ProSAVANA is an ongoing trilateral program run by the governments of Brazil, Japan and Mozambique that aims to modernize agriculture in three provinces in Northern Mozambique. PAA Africa is a multilateral partnered pilot-project that promotes local food-purchasing and school-feeding programs in Tete province, financed by governments of Brazil and the United Kingdom and executed by the United Nations' Food and Agricultural Organization (FAO) and the World Food Program (WFP). The strategies for rural territorial development that each of the programs respectively entails, their influence on national policymaking, the impacts and implications on peasant livelihoods...

Esta tese analisa o atual papel do Brasil na cooperação Sul-Sul para o desenvolvimento na África, focando na implementação e impacto das políticas brasileiras para o desenvolvimento territorial rural em Moçambique. Especificamente, dois diferentes programas para o desenvolvimento agrícola são analisados: ProSAVANA e PAA-África. O ProSavana é um programa trilateral atualmente gerido pelos governos do Brasil, Japão e Moçambique, visando modernizar a agricultura em três províncias do norte de Moçambique. O PAA África é um projeto-piloto em parceria multilateral que promove a compra de alimentos produzidos localmente para a alimentação escolar da província de Tete, sendo financiado pelos governos do Brasil e Reino Unido e executados pela United Nations' Food and Agricultural Organization (FAO) e pelo World Food Program (WFP). As estratégias para o desenvolvimento territorial rural que cada um dos programas respectivamente acarreta, sua influência na formulação de políticas nacionais, os impactos e implicações nas unidades camponesas e as concepções paradigmáticas...
Keywords: Geografia; Cooperativismo; Desenvolvimento rural - Brasil; Desenvolvimento rural - Moçambique; Geography